Economic evaluation of dialysis treatment in end-stage renal disease patients with fluid and sodium overload: Evidence from a randomized controlled trial in Thailand - Sitaporn Youngkong; Panida Yoopetch; Montarat Thavorncharoensap; Montira Assanatham; Usa Chaikledkaew; Suchai Sritippayawan (PLoS ONE, 2025)
Given the lack of cost-effectiveness information, continuous ambulatory peritoneal dialysis (CAPD) with icodextrin (CAPD+ICO) has not yet been included in the Universal Health Coverage (UHC) scheme. This study aimed to evaluate the cost-utility of dialysis treatments for end-stage renal disease (ESRD) patients with fluid and sodium overload, comparing CAPD+ICO and automated peritoneal dialysis (APD) against glucose-based CAPD. A Markov model was applied to evaluate lifetime costs and health outcomes from a societal perspective. Data, including transitional probabilities, direct medical and non-medical costs, and utilities, were collected from randomized controlled trials conducted across 16 hospitals in various regions of Thailand. Compared to glucose-based CAPD, the incremental cost-effectiveness ratio (ICER) for CAPD+ICO was 908,440 THB (26,082 USD) per quality-adjusted life year (QALY) gained, while APD was dominated, incurring higher costs and yielding fewer QALYs. The results indicated that glucose-based CAPD had a 90% probability of being the most cost-effective option from a societal perspective, based on Thailand’s willingness-to-pay (WTP) threshold of 160,000 THB (4,603 USD) per QALY gained. Therefore, CAPD+ICO is not considered a good value for money, requiring an additional annual budget of approximately 58 million THB (2 million USD). These findings provide important economic evaluation evidence to support policy decision-making alongside clinical effectiveness and equity considerations in guiding future UHC benefit package decisions for dialysis modalities among ESRD patients with fluid and sodium overload in Thailand.